Implementation of a decision aid for recognition and correction of volume alterations (Recova®) in haemodialysis patients. (1st October 2020) - Stenberg, Jenny; Lindberg, Magnus; Furuland, Hans
Abstract: Background: Fluid overload is associated with mortality in haemodialysis patients, and 30% of patients remain fluid-overloaded after dialysis. The aim of this study was to evaluate if implementation of Recova ®, a decision aid combining clinical assessment with bioimpedance spectroscopy, facilitates individualization of target weight determination and thereby contributes to improved fluid status in maintenance haemodialysis patients. Methods: The impact of the implementation was measured as the proportion of participants at an adequate target weight at the end of the study, assessed as change in symptoms, hydration status, and N-terminal pro-brain natriuretic peptide (NT-proBNP). Nurses were instructed to use Recova every 2 weeks, and the process of the intervention was measured as frequencies of fluid status assessments, bioimpedance measurements, and target weight adjustments. Results: Forty-nine patients at two haemodialysis units were enrolled. In participants with fluid overload ( n  = 10), both overhydration and fluid overload symptom score decreased. In fluid-depleted participants ( n  = 20), target weight adjustment frequency and the estimated target weight increased. The post-dialytic negative overhydration was reduced, but NT-proBNP increased. Conclusions: Implementation of Recova in haemodialysis care increased the monthly frequencies of bioimpedance measurements and target weight adjustments, and it contributed to symptom reduction. Trial registration: The Uppsala County Council Registry of Clinical Trials: FoU 2019-0001-15.